LITERATURE REVIEW: PEMANFAATAN EKSTRAK KUNYIT (CURCUMA LONGA L.) SEBAGAI INDIKATOR ALAMI DALAM DETEKSI BORAKS PADA PRODUK CIRENG - Daniel Ritonga; Khairiyah Ariqah; Mutiara Pratiwi; Desry Natalia Sidauruk; Aulia May Dinda; Syairal Fahmy Dali Munthe; Ramot Andre Samuel Purba; Salwa Hakimah Defari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Food safety is still an important issue because some food products are suspected of containing hazardous substances such as borax. Borax is often added to food to improve texture and shelf life, even though it can be harmful to human health. This study aimed to determine the potential use of turmeric extract as a natural indicator for detecting borax in cireng. The research used a literature review method by collecting and analyzing scientific articles related to borax detection using turmeric extract. The results showed that turmeric contains curcumin, a natural compound that reacts with borax and produces a color change from yellow to reddish-brown. This color change indicates the presence of borax in food samples. One cireng sample showed a reddish-brown color change and was identified as positive for borax, while another sample did not show any color change and was identified as negative. Therefore, turmeric extract can be used as a simple and environmentally friendly alternative for borax detection in food products and may increase public awareness regarding food safety.